Business Dynamics in North America Analysis of Spatial and Temporal Trade Patterns - Rajagopal (Springer International Publishing, 2018)
This book discusses the contemporary trade dynamics necessary for companies to grow competitively in the global marketplace, extending the conceptual and analytical foundations of international trade and economy in North America. This book examines the growth of international trade in North America during the pre-and post-North American Free Trade Agreement (NAFTA), and analyzes the complexities that occurred when the economic recession struck the global markets. It outlines applied tools and techniques for business projects to thrive in the competitive marketplace, and serves as a learning post and a think tank for students, researchers, and business managers operating in a global landscape. .